Designating Smoking Room to Control Environmental Tobacco Smoke in Nursing Homes - Farhang Akbar-Khanzadeh (International Journal of Occupational Hygiene, 2011)
This study was initiated to assess the effectiveness of designating smoking rooms to control environmental tobacco smoke in nursing homes. Of the 39 nursing homes located in Toledo (a city in Ohio, USA) included in the preliminary survey, 33 facilities (85%) allowed smoking, 14 facilities (36%) allowed indoor smoking, and 13 facilities (33%) provided a designated smoking area. Three of these 13 nursing homes with similar levels of care agreed to participate in study that  was more comprehensive. The levels of carbon monoxide, carbon dioxide (CO2), respirable suspended particulate matter, nicotine, and solanesol were monitored at three locations within three nursing homes: a designated smoking room with an independent ventilation system, the adjacent hallway and outside the building. The concentrations of air contaminants, except CO2, inside the designated smoking rooms were significantly higher than those in the hallways or outside. The concentration of CO2 was similar in the smoking rooms and the hallways but significantly higher than the concentration outside. The levels of ambient air temperature or relative humidity within the three locations were not generally  different. The results indicated that the designation of a smoking room with an independent ventilation system was effective in controlling the environmental tobacco smoke in these nursing homes.